BABAD PRAYUT : ANALISIS PSIKOLOGI DAN JARINGAN POLITIK ABAD KE â 1 - Joebagio, Hermanu (MIIPS, 2008)
ABSTRACTThe purpose of this research to tries to analyze the Babad Prayut, especially to analyze psychology and political network of the elites of Jawa against the political and economic changed in the 18th Century. The data were collected by primary and secondary sources of history. The primary sources was Babad Prayut, Serat Wulangreh, and Suluk Mas Nganten. The secondary sources was results of research of the 18th Century. The technique used to analyze the data was historical analysis. The result of analysis shows that: (1) in the reign of Sultan Agung, the kratons of Java were at times themselves leading agents of Islamisation, reconciliation between Javanese culture and Islamic piety, and put the large kinship by weddings; (2) that political thinking produced to legitimation, and political legitimation are determine of interpersonal trust, civic engagement, and political engagement. The third factors are symbolization of political system; (3) political change occurred in the death of Sultan Agung were many of aristocrats to prefer to collaboration with the Dutch colonial; (4) that situation make the muslim leaders took opposition. They put his self as cultural broker, merchant princes, and counter elite.